Femoral nerve block: a novel psoas compartment lateral pre‐iliac approach in dogs. (6th July 2012) - Portela, Diego A; Otero, Pablo E; Briganti, Angela; Romano, Marta; Corletto, Federico; Breghi, Gloria
Abstract Objective To describe a new approach to block the femoral nerve and to evaluate the distribution of a dye injected into the psoas compartment using a new femoral nerve block approach; to assess its clinical application, when combined with a sciatic nerve block, for surgical anaesthesia/analgesia of the pelvic limb in dogs. Study design Prospective anatomical, research and clinical study. Animals Two dog cadavers; two dogs that had to be euthanized for reasons unrelated to this study, and 15 dogs undergoing pelvic limb orthopaedic surgery. Methods Phase 1: anatomical dissections were performed to determine a simple method to approach the femoral nerve within the psoas compartment. Phase 2: 0.1 mL kg−1 of a lidocaine‐new methylene blue solution was injected bilaterally after successful electrolocation of the femoral nerve in two anaesthetized dogs. Colorant spread was evaluated through femoral nerve dissections after euthanasia. Phase 3: in 15 dogs undergoing pelvic limb orthopaedic surgery under light general anaesthesia with isoflurane, intra‐operative analgesic effect (cardiovascular responses) and early post‐operative pain score, of the novel femoral nerve block combined with a sciatic nerve block as the sole analgesic protocol, were evaluated. Results Phase 1: a needle inserted from the lateral aspect of the lumbar muscles, cranially to the iliac crest and with a 30–45° caudo‐medial direction, reaches the femoral nerve in the caudal portion of the psoas compartment. Phase 2: Four femoral nerves were stained >2 cm. Phase 3: this novel lateral pre‐iliac approach, combined with the sciatic nerve block, blunted the intra‐operative cardiovascular response to surgical stimulation in 13 out of 15 anaesthetized dogs. In addition, rescue analgesia was not required in the early post‐operative 2‐hour period. Conclusion and clinical relevance The lateral pre‐iliac femoral nerve block technique may provide adequate intra‐ and early post‐operative pain relief in dogs undergoing pelvic limb surgery.